Periportal lymphatic system on post-hepatobiliary phase Gd-EOB-DTPA-enhanced MR imaging in normal subjects and patients with chronic hepatitis C - Yamada, Yasunari; Matsumoto, Shunro; Mori, Hiromu; Takaji, Ryo; Kiyonaga, Maki; Hijiya, Naoki; Tanoue, Rika; Tomonari, Kenichiro; Tanoue, Shuichi; Hongo, Norio; Ohta, Masayuki; Seike, Masataka; et al. (Abdominal imaging, 2017)
Purpose We sought to evaluate visualization of periportal lymphatics and lymph nodes (lymphatic system) on Gd-EOB-DTPA-enhanced magnetic resonance (MR) images using a fat-suppressed T2-weighted sequence with 3-dimensional (3D) volume isotropic turbo spin echo acquisition (VISTA) at 3.0 T in normal subjects and patients with chronic hepatitis C. Methods MR imaging was performed in 254 subjects between June 2013 and May 2016. After applying inclusion and exclusion criteria, the final population was 31 normal subjects and 34 patients with chronic hepatitis C. Images were acquired after the hepatobiliary phase following intravenous administration of Gd-EOB-DTPA, which causes signal loss in the bile ducts, to facilitate the visualization of the periportal lymphatic system. Two radiologists assessed the visualization of the periportal lymphatic system in 31 normal subjects. The axial dimensions of the main periportal lymphatic system in normal subjects were measured and compared with those of 34 patients with chronic hepatitis C using the Mann–Whitney U -test, and their correlation with a hepatic fibrosis marker, the Fibrosis-4 (FIB-4), was assessed using Spearman’s rank correlation test. Results The periportal lymphatic system was detected as high signal intensity areas surrounding the portal vein up to the third branches by each reader in all normal subjects. The axial dimensions of the main periportal lymphatic system in patients with chronic hepatitis C were significantly larger than those in normal subjects ( p < 0.0001), and showed a significantly positive correlation with the FIB-4 score ( ρ = 0.73, p < 0.001). Conclusions Fat-suppressed T2-weighted MR imaging with 3D-VISTA acquired after the hepatobiliary phase on Gd-EOB-DTPA-enhanced imaging may be a useful noninvasive method for evaluating the periportal lymphatic system and the degree of hepatic fibrosis.